A new and integrated imaging and compositional method to investigate the contributions of organic matter and inorganic minerals to the pore spaces of lacustrine shale in China. (May 2021) - Gao, Zhiye; Liang, Zhu; Qinhong Hu,; Jiang, Zhenxue; Xuan, Qixiang
Abstract: Pore structure is an important factor controlling the shale gas content. Field-emission scanning electron microscopy (FE-SEM) is a commonly used shale reservoir characterization method. However, the quantitative characterization of shale pore structure based on FE-SEM results is still problematic due to the representative issue caused by strong heterogeneity at the microscale. In this study, FE-SEM images of lacustrine shale samples from the Jurassic Ziliujing Formation in the Northeastern Sichuan Basin were systematically analyzed using image processing software. The quantitative pore structure characteristics of each component (including organic matter, clay minerals, quartz and feldspar) in shale samples were extracted from the FE-SEM images. Using the areal porosity and pore size distribution from FE-SEM images, content and density of each component in shale samples and the bulk density of shale samples, the pore volume distribution of each component and the whole shale sample was calculated, which innovatively combined the FE-SEM images with shale compositional information to resolve the representative issue of FE-SEM images and was more practical. This new method could also avoid the effect of ink-bottle pores and isolated pores on shale pore structure characterization commonly existing in high-pressure mercury intrusion porosimetry (HPMIP). The results show that clay mineral pores dominantly contribute to the pore spaces of Ziliujing Formation shale, followed by quartz and feldspar pores, and organic matter (OM) pores contribute the least. The OMs are divided into four categories according to their pore sizes and morphology. More specifically, spongy pores in OM and the cracks within or along the periphery of nonporous OM are the dominant OM pore types in Ziliujing Formation shale. Furthermore, the interaction between clay minerals and organic matter could catalyze the process of pore development in OM, which is confirmed by the higher areal porosities of OMs contacting with clay minerals compared with those not. Highlights: A new method was established to obtain the pore volume curves with compositional information. Pore structures of organsic matter (OM) and inorganic minerals under FE-SEM were quantitatively characterized. The OMs contacting with clay minerals showed a higher porosity compared with those not.